A review of the species, community, and ecosystem impacts of road salt salinisation in fresh waters. (25th March 2019) - Hintz, William D.; Relyea, Rick A.
Abstract: Freshwater ecosystems worldwide are threatened by salinisation caused by human activities. Scientific attention on the ecological impacts of salinisation from road deicing salts is increasing exponentially. Spanning multiple trophic levels and ecosystem types, we review and synthesise the ecological impacts of road salt in freshwater ecosystems to understand species‐, community‐, and ecosystem‐level responses. In our review, we identify knowledge gaps that we hope will motivate future research directions. We found that road salts negatively affect species at all trophic levels, from biofilms to fish. The concentration at which road salt triggered an effect varied considerably. Species‐level impacts were generally sub‐lethal, leading to reductions in growth and reproduction, which can be magnified by natural stressors such as predation. Community‐level impacts including reductions of biodiversity were common, leading to communities of salt‐tolerant species, which may have implications for disease transmission from enhanced recruitment of salt‐tolerant host species such as mosquitoes. At the ecosystem level, road salts alter nutrient and energy flow. Contaminated wetlands could see greater export of greenhouse gases, streams will probably export more nitrogen and carbon, and lakes will encounter altered hydrology and oxygen dynamics, leading to greater phosphorus release from sediments. While it is necessary to keep roads safe for humans, the costs to freshwater ecosystems may be severe if actions are not taken to mitigate road salt salinisation. Cooperation among policy makers, environmental managers, transportation professionals, scientists, and the public will be crucial to prevent a loss of ecosystem services including water clarity, drinkable water, recreation venues, and fisheries.